2016
DOI: 10.1097/hjh.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase gene variants and their association with blood pressure and incident hypertension

Abstract: Pending confirmation, our findings suggest that variation in uric acid production, as captured by genetic variation in XOR, might be a predictor of changes in BP and in the risk of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
2
17
0
2
Order By: Relevance
“…However the studies were limited in size and careful meta-analyses may be warranted (reviewed in ( 170 )). This question of whether XO inhibitors have potential therapeutic benefit in cardiovascular disease, has been the subject of a number of clinical investigations ( 175 , 180 183 ). However, the impact of early intervention in patients with asymptomatic hyperuricemia (with or without crystal deposition) on vascular outcomes has not been definitively demonstrated ( 184 ).…”
Section: Epidemiology Of Hyperuricemia and Associated Comorbiditiesmentioning
confidence: 99%
“…However the studies were limited in size and careful meta-analyses may be warranted (reviewed in ( 170 )). This question of whether XO inhibitors have potential therapeutic benefit in cardiovascular disease, has been the subject of a number of clinical investigations ( 175 , 180 183 ). However, the impact of early intervention in patients with asymptomatic hyperuricemia (with or without crystal deposition) on vascular outcomes has not been definitively demonstrated ( 184 ).…”
Section: Epidemiology Of Hyperuricemia and Associated Comorbiditiesmentioning
confidence: 99%
“…Increased XO activity, rather than SUA, could be responsible for an adverse cardiovascular outcome. In line with this hypothesis, a recent study examined several XO gene variants in a prospective cohort of 2500 European participants and found three minor alleles associated with increased risk of hypertension [77]. Despite the enzymatic activity controlled by these variants being uncertain, another a longitudinal cohort study of 246 Dutch children (mean age 7 years) [78], led by the same investigator, showed that XO activity, estimated by a ratio of purine to uric acid, was associated with blood pressure.…”
Section: Hyperuricaemia and Cardiovascular And Renal Diseasesmentioning
confidence: 99%
“…These results contrast with Mendelian randomization studies that have examined genetic polymorphisms involved in the renal handling of uric acid and that suggest these genes most likely do not directly increase the risk of cardiovascular disease [9]. More recent studies have investigated the relevance of genetic polymorphisms affecting xanthine oxidoreductase (XOR)-activity, with disparate conclusions [10,11].…”
Section: Introductionmentioning
confidence: 81%